2023
DOI: 10.3389/fvets.2022.1104152
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of cannabidiol following single oral and oral transmucosal administration in dogs

Abstract: IntroductionIn the last few years, different formulations containing cannabidiol (CBD) were tested with regard to its efficacy on chronic pain, refractory epilepsy, anxiety, aggressive behavior and atopic dermatitis in dogs. CBD is generally administered orally, but its low bioavailability, probably due to a first-pass metabolism, represents a great limitation. The aim of this study was to evaluate if CBD bioavailability increases after oral transmucosal administration (OTM) compared to oral treatment.MethodsT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 29 publications
0
16
0
Order By: Relevance
“…[ C max ]/IC 50 values greater than 1.0 indicate that clinically relevant inhibition is likely; values between 0.1 and 1.0 indicate that inhibition is possible; while values less than 0.1 indicate that the likelihood of inhibition is remote. Table 2 provides [ C max ]/IC 50 values calculated using the highest average CBD and CBDA C max values reported in the literature for dogs administered cannabinoids at doses ranging from 1 to 10 mg/kg orally (Della Rocca et al, 2022; Doran et al, 2021; Wakshlag et al, 2020). As shown in Table 2, [ C max ]/IC 50 ratios between 0.1 and 1.0 were observed for tramadol N ‐demethylation inhibition by all cannabinoids tested, and for tramadol O ‐demethylation inhibition by CBDA and CBDAX.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[ C max ]/IC 50 values greater than 1.0 indicate that clinically relevant inhibition is likely; values between 0.1 and 1.0 indicate that inhibition is possible; while values less than 0.1 indicate that the likelihood of inhibition is remote. Table 2 provides [ C max ]/IC 50 values calculated using the highest average CBD and CBDA C max values reported in the literature for dogs administered cannabinoids at doses ranging from 1 to 10 mg/kg orally (Della Rocca et al, 2022; Doran et al, 2021; Wakshlag et al, 2020). As shown in Table 2, [ C max ]/IC 50 ratios between 0.1 and 1.0 were observed for tramadol N ‐demethylation inhibition by all cannabinoids tested, and for tramadol O ‐demethylation inhibition by CBDA and CBDAX.…”
Section: Resultsmentioning
confidence: 99%
“…Ratios of maximal observed plasma cannabinoid concentration [ C max ] to in vitro IC 50 values were calculated for each cannabinoid and each P450 selective enzyme activity as a preliminary indicator of the likelihood of in vivo drug–drug interactions (Bjornsson et al, 2003). A review of the literature identified three pharmacokinetic studies in dogs that reported CBD C max values (Della Rocca et al, 2022; Doran et al, 2021; Wakshlag et al, 2020) and one study that reported CBDA C max values (Wakshlag et al, 2020). For the calculation of cannabinoid inhibitor [ C max ]/IC 50 ratios, we used the highest reported mean CBD C max value (226 ng/mL; 0.72 μM) and the highest reported mean CBDA C max value (510 ng/mL; 1.42 μM), which were both from the study by Wakshlag et al (2020).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Variation in the PK pattern of plasma CBD arises from an extensively first-pass metabolism and its low aqueous solubility that leads to poor bioavailability and a poor biological effect ( 12 , 14 ). Commonly, inconsistent and variable systemic drug exposure are affected by multiple factors, including route of administration, dosage form, dose range, and health and feeding status.…”
Section: Discussionmentioning
confidence: 99%
“…Oral bioavailability of CBD in dogs has been reported to be lower than 20% ( 13 ). Notably, it was hypothesized that the first-pass metabolism is one of major concerns regarding the low bioavailability of CBD via oral administration ( 14 ). Therefore, there has been much interest to increase the CBD plasma level and to identify alternative routes and different dosage forms of administration.…”
Section: Introductionmentioning
confidence: 99%